High serum zinc levels in HELLP syndrome (Annals of Medical Research, 2022)
Aim: HELLP syndrome is a possibly fatal complication of severe preeclampsia that occurs throughout pregnancy. Biochemical abnormalities are one of the hypotheses proposed to explain the disease's physiopathological symptoms. According to studies, different congenital illnesses are caused by a lack of nutrients such as zinc, copper, iron, manganese, and folic acid, the demand for which increases during pregnancy. The objective of this study was to compare serum zinc and copper levels in healthy women and pregnant women with HELLP, as well as to investigate if there was a relationship between the two.Materials and Methods: The serum zinc and copper levels of 20 healthy pregnant women and 20 pregnant women with HELLP were measured using an Atomic Absorption Spectrophotometer.Results: Serum Zn levels in HELLP syndrome patients were significantly higher than in healthy pregnant women (p